Oncologic Management of Hereditary Colorectal Cancer - Yacoub, George; Nagalla, Srikanth; Aklilu, Mebea (Clinics in Colon and Rectal Surgery, 2012)
Colorectal cancer (CRC) is the second most common cancer in females and the third most common cancer diagnosed in males. Familial CRC comprises ~20 to 30% of all CRC cases. Lynch syndrome (LS), previously called hereditary nonpolyposis CRC (HNPCC), is the most common of the hereditary CRC syndromes. In this review, the oncological management of hereditary colorectal cancer from the medical oncologist perspective is discussed with special emphasis on Lynch syndrome. Lynch syndrome is characterized by the presence of germline mutations in the mismatch repair genes (MMR)-MSH2, MLH1, MSH6, and PMS2. The available data regarding the prognostic role of mismatch repair genes (MMR), the predictive role of MMR genes, and the implications of that in the management of patients with deficient MMR genes (dMMR/MSI-H) tumors including Lynch syndrome patients are also discussed.
Keywords: hereditary colorectal cancer; Lynch syndrome; microsatellite instability; chemotherapy